KhiyÄr alË—Majlis dan Aplikasinya dalam Jual Beli Modern (Studi Komparatif Pandangan Jumhur Ulama dan Imam Malik) - Muhammad Taufan Djafri; Patahuddin, Askar; Ridha, Muhammad (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This article aims to find out the jurisprudence khiyÄr alË—majlis according to Imam Malik and Jumhur Ulama, and to know the application of khiyÄr alË—majlis in modern buying and selling. This study uses qualitative methods with library research (library research) with content analysis of the selected data sources. The research results obtained: First, according to the Jumhur Ulama khiyÄr alË—majlis can be done either in person or online. Second, According to the Maliki School of KhiyÄr al-Majlis it is not allowed and what can be done is KhiyÄr. Requirements before transactions such as delivery of goods, as well as KhiyÄr disgrace when a buyer finds a deficiency / defect in the goods that have been purchased. Third, the application of KhiyÄr al-Majlis in modern buying and selling or online shop in the form of the right to continue or cancel the sale and purchase between the seller and the buyer, this can be done if one of the two requires a khiyar within a certain time and they are still in one transaction until he / she is receive the goods and this is in accordance with the opinion of the jumhur ulama, whereas according to Imam Malik it is not allowed because this can damage the terms of sale and purchase.